Preweaning nutritional effects of supplements on performance of suckling beef calves grazing tropical pastures - Carvalho, Victor Valério de (2018)
For this thesis, two chapters were prepared based on studies with Nellore cow-calf pairs, submitted to different creep-feeding supplementation strategies. In the fisrt chapter forty Nellore cow-calf pairs (iBW= 131±3.5 kg, 3 mo of age) and their respective dams (iBW = 457±9.3 kg, 7 yr of age) were randomly assigned to Brachiaria decumbens pastures (CP, 89 g/kg DM; NDF, 572 g/kg DM) to evaluate the effects of supplements with increasing RUP contents on nutritional and productive performance, and metabolic responses. The treatments were: control (no supplement) and supplements with similar CP content (230 g/kg DM) and increasing levels of RUP (Low = 94; Medium = 132 and High = 170 g RUP/kg DM) fed at 10 g/kg BW. Supplemented calves had greater intake of DM, CP and TDN intake compared with control calves, but there were no differences among calves fed supplments with the increasing RUP levels. The supplements RUP levels had no adverse effect on forage intake nor in fibre and organic matter digestibility, neither on rumen microbial protein synthesis. Increasing the supplement RUP content linearly decreased mRNA expression of genes associated with liver ureagenesis, carbamoyl phosphate synthetase (CPS) and argininosuccinate synthetase (AS), with a concurrent linear decrease in serum urea-N concentration (SUN) and urinary urea-N excretion (U. However, there was no effect mRNA expression of genes associated with liver gluconeogenesis (phosphoenolpyruvate carboxykinase, PEPCK) among supplemented calves, which parallels the lack of treatment effect for serum glucose and insulin concentrations. Moreover, no differences were detected for T3 and T4 serum concentration. Supplemention increased (<0.01) calves average daily gain (⁓ 0.997 vs. 0.793 kg/d), and weaning weight (⁓270 vs. 241 kg), in which ultrasound carcass traits (REA and SFT) traits were also greater than non-supplemented calves, however, these variables were similar among supplemented calves. These results indicates that increasing the supplement RUP contents had no adverse effect on calves' intake and digestibility. In addition, as supplement RUP level increased, mRNA expression liver ureagenesis, UUN and SUN decreased, which indicates a better N use efficiciency, though all supplements provided similar performance. The second chapter aimed to evaluate the effects of creep-feeding supplementation on growth performance and efficiency, feed intake and digestibility by Nellore calves grazing tropical pastures, using a meta-analytical approach. The dataset were collected from 18 studies, which were carried out between 2007 and 2017, totaling 75 treatment means that represented 832 cow-calf pairs. All studies had a control treatment with no creep-feeding supplementation (non creep-fed calves), and a wide variety of creep-feeding treatments (creep-fed calves), that were evaluated herein as daily amount of supplement intake (SUP, g/kg BW, DM basis) and supplemental crude protein intake (SCPI, g/kg BW); whereas dependent variables were evaluated as differential values relative to non creep-fed calves. Forage DM intake (g/kg BW) decreased linearly as SUP increased, whereas milk DM intake (g/kg BW) were not affected, though total DM intake increased linearly. The fibre digestibility responded quadratically to SUP and SCPI; however, DM digestibility and TDN intake increased linearly as SUP increased. The supplemental weight gain (SWG) responded quadratically as SUP (P < 0.01) and SCPI (P < 0.01) increased, and there was an influence of calf' sex. The maximum responses were estimated at 7.6 g/kg BW (0.2 kg/d) for bull calves, and at 5.5 g/kg BW (0.1 kg/d) for heifer calves. The calculated supplement crude protein content for maximal responses were 225 and 224 g CP/kg DM for bull and heifer calves respectively. Likewise, supplemental feed efficiency responded quadratically to SUP and SCPI levels. We conclude that creep-feeding improves preweaning weight gain, in which calves responds differently according to sex. Nonetheless, the best results in supplemental weight gain is achieved with moderate amounts of protein supplements.